Indian Kapok - Ghose, T. P. (Indian Forester, 1943)
The demand for kapok has increased considerably both for the manufacture of life-belts and other life-saving appliances as well as for its newer uses like the manufacture of felted kapok and kapok textilor yarn. The Java kapok (Ceiba pentandra floss) used to meet the bulk of the demand, and the Indian kapok (Bombax malabarimm floss), which at one time used to be considered as of inferior quality, has now been recognised as equal to the Java kapok in buoyancy, weight-bearing capacity and freedom from water-logging and its use in making life-belts. Etc., has been approved of both by the Mercantile Marine Department. Calcutta and the Marine Surveyors of the British Ministry of Transport. The above, coupled with the fact that supplies from Java have now stopped, have opened enormous commercial possibilities for the Indian kapok. Detailed infonnation on Indian kapok is given and attention of all concerned is being drawn to the necessity of increasing the production and of marketing kapok of high standard, free from adulteration.